2020
DOI: 10.2139/ssrn.3603228
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Home Advantage in English Professional Football; 1973-2018

Abstract: We study seasonal home advantage in English professional football over the period 1974 to 2018. We distinguish between absolute home advantage, enjoyed equally by all teams in a division, and relative home advantage, which differs among teams in the division. We find that absolute home advantage is substantial, ranging from 0.59 to 0.64 in terms of points per game or 0.44 to 0.46 in terms of goal difference. Likewise, clubs differ substantially in the relative home advantage they enjoy. Relative home advantage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 17 publications
3
18
0
Order By: Relevance
“…It is notable that the HA before lock-down in 2019/20 was less than in the season before, and also less than reported in literature (e.g., Pollard and Gómez, 2014a with 58.35% for 2006–2012), but not significantly different. This is in accordance with a reported general decline in HA (Pollard, 2008 ; Peeters and van Ours, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It is notable that the HA before lock-down in 2019/20 was less than in the season before, and also less than reported in literature (e.g., Pollard and Gómez, 2014a with 58.35% for 2006–2012), but not significantly different. This is in accordance with a reported general decline in HA (Pollard, 2008 ; Peeters and van Ours, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…Home advantage (HA), quantified by the number of points won at home expressed as a percentage of all points at home and away (Pollard, 1986 ; Pollard and Gómez, 2014b , 2015 ), is a well-studied phenomenon in soccer. Despite a decline in the last decades, probably due to increased professionalism, distancing of players from fans, and globalized marketing strategies that decreased the identification of the local community with clubs (Smith, 2003 ; Pollard, 2006a ), HA is still present in professional soccer (Peeters and van Ours, 2020 ). A crucial assumption for calculating the HA is a balanced schedule, meaning that all teams play two games against each other, one at home and one away (Pollard and Gómez, 2014b ).…”
Section: Introductionmentioning
confidence: 99%
“…Bryson and colleagues 39 , demonstrated that the HA reduction is considerably larger when the previous seasons are included than when only the 2019/20 season is used for the analysis. This is in line with the observed phenomenon of decreasing HA over time 68 and was possibly a reason for the high estimates in some of the studies 48,51 .…”
Section: Comparison With Other Studies and Partial Attendancesupporting
confidence: 87%
“…Second, an objective understanding of how the home team’s strength (relative to the opposition and within league merit positions) and the difficulty of their fixture schedule in terms of the opposition they face may impact the effects observed for HA, is missing from the literature. This is important as the quality of opposition a team faces is indicative of their likelihood of winning ( Peeters & van Ours, 2020 ), and more skilled sides may well rely less on their crowds’ support than their less-skilled counterparts. Third, the impact of unmeasured confounds has also not been fully considered, and while a number do exist which we cannot control for in this study (e.g., COVID infections, country-level heterogeneity in response to the pandemic, differences in training schedules, etc.…”
Section: Introductionmentioning
confidence: 99%